Predicting the behavior of young voters in elections: a case study of governor election in Jakarta, Indonesia - Astuti, Prida Ariani Ambar; Hangsing, P. (Penerbit Universiti Kebangsaan Malaysia, 2018)
Young people have often been categorised as a group apart from conventional politics, and this disengagement contributed to the growing sense of apathy even alienation towards politics. The biggest obstacle for young people to get involved in politics is their negative view of the politicians is perceived by many young people that they do not care and no attempt to address the issues that matter to them. Nevertheless, since 2012, there has been a significant change in Indonesia. At the Jakarta Governor Election 2012, the number of young voters who voted was increasing. Therefore, the content of the media, which is the basis of media effects, is necessary to be investigated. Researchers use content analysis on Facebook, Twitter, YouTube and online game ‘Save Jakarta’ to find out the messages conveyed by the winning candidate. The content of social media was viewed based on three coding categories: information, engagement, and online participation. Furthermore, data collected from documentation of conversations or manifest content that appeared in social media during the Jakarta Governor Election Campaign 2012 became a technique of data collection, and the descriptive statistical calculation will be used to analyze the data. The findings in this study are information about the candidates, campaigns, and election process can be conveyed to voters to help improve their knowledge, which also keep their reminded. Ultimately, this information is expected to make voters like candidates then trust.